P158 Diagnostic yield of different imaging modalities (VCE, MRE and SBUS) in paediatric Inflammatory Bowel Disease patients. (27th May 2021) - Kurteva, E; Rendo, G; Ahmad, T; Watson, T; Jones, K; Gaynor, E; Kiparissi, F
Abstract: Background: Wireless Video Capsule Endoscopy (VCE), Magnetic resonance enterography (MRE) and Small Bowel ultrasound (SBUS) are well-established diagnostic tools, used in the evaluation of small bowel disease in paediatric inflammatory bowel disease (IBD) patients.The aim of this study was to compare VCE findings with those of MRE and SBUS and evaluate discrepancies between them. Methods: VCE examinations were conducted in histologically confirmed paediatric IBD patients in a period of 19 months (March 2018 – November 2019) in a tertiary center. The VCE findings were retrospectively compared to relevant findings on MRE and SBUS, collected from electronic data records. Results: 34 patients were included in the study (16 males, 18 females) with an age range at the moment of diagnostic assessment between 4–17 years (median 12 years). 21 patients were diagnosed with Crohn disease (CD), 9 patients with Ulcerative Colitis (UC) and 4 patients with IBD Unclassified (IBD-U). 8/34 (23.5%) patients were found to have all three diagnostic investigations, 21/34 (61.8%) had MRE and 21/34 (61.8%) had SBUS. Concordance between the three modalities were seen in 5/8 (62.5%) patients. Of these, 3/5 (60%) had no small bowel disease identified on VCE, MRE and SBUS, while in 2/5 patients (40%) the same distribution of small bowel disease was identified using all three diagnostic modalities. When comparing VCE to MRE, differing distributions of disease were seen in 10/21 patients (47.6%). 6/10 (60%) had terminal ileitis, 2/10 (20%) had ceacal disease and 3/10 (30%) jejunal disease noted on MRE, but with no disease identified on VCE. 1/10 patient (10%) had a normal MRE but duodenal and proximal jejunal ulceration was reported on VCE. VCE and SBUS had a higher concordance (71.4%) in identifying disease distribution. In 6/21 patients (28.5%) there was a discrepancy in the findings reported on SBUS when compared to VCE.Of these, 4/6 (66.7%) had a normal SBUS but small bowel disease (jejunal and ileal disease) on VCE.1/6 patient (16.7%) had caecal inflammation and 1/6 (16.7%) had active terminal ileitis on SBUS, which was not reported on their VCE. Conclusion: The identification of small bowel disease is essential in the diagnosis and subsequent management of paediatric IBD. VCE, MRE and SBUS are established modalities to detect intestinal disease. This study demonstrates that performing all three diagnostic modalities may have important practical significance and increase diagnostic yield in detecting small bowel inflammatory bowel disease.